Breaking of Dormancy and Multiple Shoot Formation of Curcuma Cordata - Sulaiman Yahya, Muhammad Ridwan (2003)
This study was to determine the effects of different plant growth regulators (PGRs) on breaking of dormancy and induction of multiple shoot formation from rhizomes of Curcuma cordata. This study comprised of four experiments. The first experiment was conducted to evaluate the effect of different PGRs at various concentrations on breaking of dormancy of rhizomes of C. cordata. The PGRs used were IBA (0, 250, 500 and 750 mgL -1), GA3 (0, 500, 1000 and 1500 mgL -1), SAP (0, 100, 200 and 300 mge1), ethephon (0,250,500 and 750 mgL-1) and daminozide (0,500,1000 and 1500 mgL-1). The second experiment analyzed the influence of light intensity and 6-benzylaminopurine (BAP) on breaking of dormancy of C. cordata. The light intensities were: 18 molm-2s-1, 9.3 molm-2s-1, 4.4 molm-2s-1, 2.4molm-2s-1, 1m01m-2s-1 and 0 molm-2s-1, respectively. The third experiment analyzed the effect of different PGRs with sucrose at various concentrations on breaking of dormancy of rhizomes of C. cordata.